Предмет: Алгебра, автор: katosik96

помогите решить, пожалуйста ​

Приложения:

Ответы

Автор ответа: сок111213
2

x {}^{2}  - 4x + 2 = 0 \\ x_{1} + x_{2}  = 4\\ x_{1} \times x_{2} = 2 \\ x {}^{2} _{1} +x {}^{2} _{2} = x {}^{2} _{1} +2x_{1}x_{2} + x {}^{2} _{2} -  2x_{1}x_{2}   \\  (x  _{1} +x _{2}) {}^{2}  - 2x_{1}x_{2 }   \\  \frac{2}{x {}^{2} _{1}}  +  \frac{2}{x {}^{2} _{2}}  =  \frac{2(x {}^{2} _{1} +x {}^{2} _{2}) }{(x  _{1} \times x  _{2}) {}^{2} }    =  \\  \frac{2((x  _{1} +x _{2}) {}^{2}  - 2x_{1}x_{2 }  )}{(x_{1} \times x_{2}) {}^{2} }  =  \\  \frac{2( {4}^{2}  - 2 \times 2)}{ {2}^{2} }  =  \\  \frac{16 - 4}{2}  =  \frac{12}{2}  = 6


katosik96: большое спасибо!!
Похожие вопросы
Предмет: Физика, автор: 55560321